Economic Strategies and Resilience of Internally Displaced Persons in Greater-Kasaï (DRC): An Analysis of Survival Mechanisms, Community Dynamics, and Structural Barriers (British Journal of Multidisciplinary and Advanced Studies, 2025)
Abstract: This study examines the economic strategies and resilience of Internally Displaced Persons (IDPs) in Greater-Kasai (DRC), a region scarred by protracted conflict and humanitarian crises. It investigates informal survival mechanisms (subsistence farming, petty trade, crafts), community networks, and structural barriers (insecurity, land scarcity, institutional gaps).Methodology: Mixed-methods approach (quantitative surveys, qualitative interviews, participatory mapping) grounded in theories of informal economies and social capital.Key Findings:• 87% of IDP income derives from the informal sector, yet with heightened vulnerability.• Women (53.2% of IDPs) drive resilience but face disparities (limited credit access, unpaid labor).• Community networks (cooperatives, savings groups) enhance stability but lack legal recognition.• Humanitarian aid is critical but risks dependency without sustainable solutions (microfinance, land reform).Recommendations:• Formalize informal economies through legal cooperatives.• Improve access to land and basic services (water, education).• Mainstream IDPs into local development plans.• Implement gender-responsive interventions to empower women.